Population participation: a social bet for the sustainable management of residential waste,: The SAHELVillage; experience in Tizi-Ouzou - Benazzouz, Aicha; Bouadam, Roukia (Journal of Human Sciences, 2020)
The involvement of inhabitants constitutes the approach that enables members of civil society to participate in the process of management through compliance with directives and decisions. The experience of the "Sahel" village in Tizi-Ouzou city depended heavily on this approach in the field of household waste management. Therefore, this paper aims through analyzing this experiment, to highlight the effectiveness of the social bet and to attempt to measure citizenship and spirit of belonging in the field of sustainable management of household waste. To conduct our research ,we have adopted field investigation and direct observation, in addition to the field interviews with the various actors, and we also supported our research with a field questionnaire to reach quantitative and qualitative results.